Determinants of short-term blood pressure variability – the value of arterial stiffness - Olena Kanishcheva; Oleksandr Bilchenko (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. Increased blood pressure variability is a significant parameter that affects the prognosis in patients with arterial hypertension, and is an independent predictor of cardiovascular events and mortality. The arterial elasticity is an important factor in maintaining a constant average blood pressure for adequate blood supply to inner organs against the background of dynamic blood pressure fluctuations. A decrease in the elastic properties of the arteries, and therefore, an increase in the arterial stiffness can be one of the potential mechanisms for the blood pressure variability violation. Objective. The aim of the study was to evaluate the possible relationships between arterial stiffness indicators and blood pressure variability indices in patients with hypertension based on the results of ambulatory blood pressure monitoring. Patients and methods. The results of ambulatory blood pressure monitoring of 172 patients with hypertension were analyzed. Arterial stiffness was assessed using the ambulatory arterial stiffness index - symmetric and asymmetric. SD, SDw, CV, SV, ARV, and BPVR indices were calculated to assess blood pressure variability. Analysis of the obtained results was carried out using Microsoft Excel 2010 and the STATISTICA version 10.0 software. Differences between groups were assessed by the Mann-Whitney method, correlations among blood pressure variability indices and ambulatory arterial stiffness indices were evaluated using Spearman`s rank correlation analysis. Significance was set at p ˂ 0.05. The results. Awake asymmetric ambulatory arterial stiffness index was significantly higher than asleep one, no statistically significant difference between asleep and 24-hour asymmetric ambulatory arterial stiffness index was established. The asleep symmetric ambulatory arterial stiffness index did not significantly differ from the awake one and was significantly higher than the 24-hour one. In comparison with asymmetric, for symmetric ambulatory arterial stiffness index statistically significant relationships were established for a greater number of blood pressure variability indices. In all statistically significant cases, the direction of the established relationship with arterial stiffness was only direct for the systolic blood pressure variability indices. Variability of diastolic blood pressure had a clear inverse relationship with arterial stiffness. Conclusions. The presence of pathogenetic interrelationships between arterial stiffness and blood pressure variability have been proven in the present study. The obtained results allow to state that arterial elasticity is an important component of blood pressure variability.